EVALUATION OF THE EFFECTIVENESS OF PHYTOMELIORATIVE MEASURES ON STRONGLY SALINE SOILS (Spectrum Journal of Innovation, Reforms and Development, 2022)
The article presents the results of experiments on the cultivation of phytomeliorant plants in 2009-2011 in order to rationally use water resources in the Bukhara oasis with increasing water shortages, the introduction of water-saving technologies in irrigation and saline washing.